LEGAL CERTAINTY IN COASTAL ZONING FOR LOCAL WISDOM-BASED SEAWEED INDUSTRY DEVELOPMENT IN THE BLUE ECONOMY - Yuliana, Adelia; Sakti, Muthia (International Journal of Cultural and Social Science, 2025)
Indonesia’s coastal governance is characterized by jurisdictional overlaps and normative inconsistencies, which undermine the legal framework sustaining the seaweed sector within the Blue Economy paradigm. Employing a normative-doctrinal method, this study adopts the principle of legal certainty in coastal spatial planning and evaluates the scope of regional governments’ competence in integrating local wisdom into marine resource regulation. The analysis reveals that the centralization of authority under Law No. 6 of 2023 generates normative disharmony with Law No. 23 of 2014, thereby restricting provincial administrative jurisdiction over maritime affairs. This recentralization engenders regulatory dualism, overlapping licensing regimes, and weakens legal safeguards for coastal communities. In contrast, regional governments advance sustainable governance by institutionalizing local wisdom through participatory and empowerment-based mechanisms, which reconcile ecological imperatives with economic objectives. The study concludes that regulatory harmonization and juridical recognition of local wisdom are essential for equitable and sustainable marine development.